2014
DOI: 10.1063/1.4904428
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity enhancement of oxide skins in reversible Ti-doped NaAlH4

Abstract: The reversibility of hydrogen sorption in complex hydrides has only been shown unambiguously for NaAlH4 doped with transition metal compounds. Despite a multitude of investigations of the effect of the added catalyst on the hydrogen sorption kinetics of NaAlH4, the mechanism of catalysis remains elusive so far. Following the decomposition of TiCl3-doped NaAlH4 by in-situ X-ray photoelectron spectroscopy (XPS), we link the chemical state of the dopant with those of the hydride and decomposition products. Titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A fundamental breakthrough came with the discovery by Bogdanović and Schwickardi that doping sodium aluminum hydride with titanium not only improves the kinetics of dehydrogenation reaction but also makes the reaction reversible . Since then, the decomposition and reabsorption of hydrogen in the NaAlH 4 system has been one of the most intensively investigated reactions in the field of solid hydrogen storage materials. Much of this research has been devoted to the confinement of this complex hydride in different host matrices, with some interesting effects which are discussed in the following section.…”
Section: Classes Of Nanostructured Metal Hydridesmentioning
confidence: 99%
See 2 more Smart Citations
“…A fundamental breakthrough came with the discovery by Bogdanović and Schwickardi that doping sodium aluminum hydride with titanium not only improves the kinetics of dehydrogenation reaction but also makes the reaction reversible . Since then, the decomposition and reabsorption of hydrogen in the NaAlH 4 system has been one of the most intensively investigated reactions in the field of solid hydrogen storage materials. Much of this research has been devoted to the confinement of this complex hydride in different host matrices, with some interesting effects which are discussed in the following section.…”
Section: Classes Of Nanostructured Metal Hydridesmentioning
confidence: 99%
“…Apart from simple metals, positive effects of surface oxidation have also been proposed in the context of the complex metal hydrides NaAlH 4 and LiBH 4 . Using in situ XPS, Delmelle et al examined the formation and evolution of surface oxides on NaAlH 4 during dehydrogenation . They identified the formation of Al 2 O 3 and Ti 2 O 3 during decomposition of TiCl 3 -doped NaAlH 4 and attributed the enhanced dehydrogenation kinetics to the high hydrogen mobility within these oxides species near the surface.…”
Section: Mechanistic Effects Of Nanosizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface oxides could also play a more direct role in the surface reactions themselves. This possibility was suggested by Delmelle et al, who studied the role of oxide surface contamination in the dehydrogenation of Ti-doped NaAlH 4 using in situ X-ray photoelectron spectroscopy (XPS). Based on the evolution of Ti, Al, and O XPS spectra, and using reference XPS binding energies to identify features corresponding to NaAlH 4 , Al 2 O 3 , and metallic Al, they suggested that oxygen shuttles reversibly between titanium and aluminum oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The various different concepts used to overcome the kinetic barriers may be simplified by: 1. removing the static interface 2. improving the static interface 3. removing the dynamic interface 4. improving the dynamic interface A static interface is often the surface such as the oxide skin on MgH 2 blocking hydrogen dissociation and transport. Its removal [concept 1)] is only a theoretical option, as there are always contaminants in technical hydrogen (Delmelle et al (2014)). Concept 2) is the only option.…”
Section: Concepts To Improve Interfaces In Energy Materialsmentioning
confidence: 99%